Avaliação e reabilitação de crianças asmáticas nos desfechos funcionais, autonômicos e inflamatórios - Gomes, Évelim Leal de Freitas Dantas (2013)
Background: Asthma is the most common chronic respiratory disease in childhood. The most striking feature is the persistent inflammation of the airways, even in periods of crisis. The imbalance between the pro and anti-inflammatory mechanisms are responsible for this chronic inflammation as an autonomic dysfunction that exerts an important influence on pathogenesis and control of the disease. The impact of these changes takes these children a patho-physiological cycle of underactive and sedentariness influencing on functional capacity and making the control of the disease worse. Objectives: to evaluate the autonomic modulation of asthmatic children in crisis and in stable phase, the effect of continuous positive airway pressure (CPAP) on airway permeability and autonomic modulation, evaluate the response of the autonomic nervous system (ANS) is at maximum and submaximal exercise and assess the effectiveness of a rehabilitation programme with active video game. Methods: 3 cross-sectional studies and a clinical trial were carried out, in which were evaluated 40 asthmatic children who underwent pulmonary function test (PFT), exhaled Nitric Oxide (FeNO), exercise testing (ET), respiratory muscle strength assessment (RMS), heart rate variability (HRV), Incremental Shuttle Walk Test (ISWT), 3-minute step test (ST3), Asthma control questionnaire (ACQ6), anthropometric measurements and tetrapolar bioelectrical impedance. Results: it was found a prevalence of sympathetic nervous system on asthma crisis unlike the stable phase, in which there is predominance of the parasympathetic nervous system. During the maximum test of asthmatic children hasn t had vagal withdrawal. The peak flow has increased after the withdrawal of CPAP, translating as possible, in addition to the mechanical effect bronchodilation positive pressure. Training with active video game caused a maximum expenditure of energy, bigger than on the treadmill, and featured improved functional capacity and lung inflammation. Conclusion: there is a difference in the autonomic modulation of asthmatic children in stable phase and during the crisis, as well as ANS's response to maximum physical effort when compared to the submaximal exercise. The CPAP promoted a possible bronchodilation, besides the mechanical effect; Is possible perform aerobic training with active video game, with positive outcome in lung inflammation.